Growth Rate and Cell Size Modulate the Synthesis of, and Requirement for, G(1)-Phase Cyclins at Start - Schneider, Brandt L. (American Society for Microbiology, 2004)
In Saccharomyces cerevisiae, commitment to cell cycle progression occurs at Start. Progression past Start requires cell growth and protein synthesis, a minimum cell size, and G(1)-phase cyclins. We examined the relationships among these factors. Rapidly growing cells expressed, and required, dramatically more Cln protein than did slowly growing cells. To clarify the role of cell size, we expressed defined amounts of CLN mRNA in cells of different sizes. When Cln was expressed at nearly physiological levels, a critical threshold of Cln expression was required for cell cycle progression, and this critical threshold varied with both cell size and growth rate: as cells grew larger, they needed less CLN mRNA, but as cells grew faster, they needed more Cln protein. At least in part, large cells had a reduced requirement for CLN mRNA because large cells generated more Cln protein per unit of mRNA than did small cells. When Cln was overexpressed, it was capable of promoting Start rapidly, regardless of cell size or growth rate. In summary, the amount of Cln required for Start depends dramatically on both cell size and growth rate. Large cells generate more Cln1 or Cln2 protein for a given amount of CLN mRNA, suggesting the existence of a novel posttranscriptional size control mechanism.